Predictors of diabetes self-management among type 2 diabetes patients in Kuching and Samarahan divisions - Azylina, Gunggu (Universiti Malaysia Sarawak (UNIMAS), 2015)
Diabetes mellitus (DM) is a significant global health problem and the prevalence of type 2 diabetes mellitus in Malaysia has increased by 31.0% over the period of five years (2006 – 2011). Uncontrolled DM often leads to many complications such as heart disease, stroke, renal problem, amputation and blindness, thus, adherence to diabetes self-management (DSM) is the cornerstone in diabetes management. Incorporating DSM regimens which includes taking medications, engaging in physical activity, regulating diet, foot care and self-monitoring of blood glucose into daily routine among type 2 diabetes people is essential to maintain good glycaemic control. However, performance of DSM in Malaysia is suboptimal and yet to be studied locally in Sarawak, Malaysia. Therefore, this cross-sectional study aimed to determine the current status of DSM and the predicting factors. A total of 400 respondents participated in the study who were recruited from four randomly selected governments’ diabetes clinics at Kuching and Samarahan Divisions. Among four DSM assessed in the study, taking oral anti-diabetic medication account for 84.2%, whereas engaging in physical activity showed the lowest percentage (29.1%). Performing foot care and diet control were reported at 33.5% and 60.8% respectively. Fasting blood sugar, belief in treatment effectiveness, family support and knowledge were predictive of DSM performance (R2 = 0.165; F=15.56; p < 0.001). The findings of this study provided further information about the current DSM status and the predictors that affect the behaviour. Healthcare members who manage patients with type 2 diabetes mellitus should consider those predictors in their diabetes management.